IgE recognition patterns in peanut allergy are age dependent: perspectives of the EuroPrevall study. Issue 4 (April 2015) - Ballmer‐Weber, B. K.; Lidholm, J.; Fernández‐Rivas, M.; Seneviratne, S.; Hanschmann, K.‐M.; Vogel, L.; Bures, P.; Fritsche, P.; Summers, C.; Knulst, A. C.; Le, T.‐M.; Reig, I.; et al.
Abstract: Background: We tested the hypothesis that specific molecular sensitization patterns correlate with the clinical data/manifestation in a European peanut‐allergic population characterized under a common protocol. Methods: Sixty‐eight peanut‐allergic subjects and 82 tolerant controls from 11 European countries were included. Allergy to peanut and lowest symptom‐eliciting dose was established by double‐blind placebo‐controlled food challenge in all but anaphylactic subjects. Information of early or late (before or after 14 years of age) onset of peanut allergy was obtained from standardized questionnaires. IgE to peanut allergens rAra h 1–3, 6, 8–9, profilin and CCD was determined using ImmunoCAP. Results: Seventy‐eight percent of peanut allergics were sensitized to peanut extract and 90% to at least one peanut component. rAra h 2 was the sole major allergen for the peanut‐allergic population. Geographical differences were observed for rAra h 8 and rAra h 9, which were major allergens for central/western and southern Europeans, respectively. Sensitization to rAra h 1 and 2 was exclusively observed in early‐onset peanut allergy. Peanut‐tolerant subjects were frequently sensitized to rAra h 8 or 9 but not to storage proteins. Sensitization to Ara h 2 ≥ 1.0 kUA /l conferred a 97% probability for a systemic reaction ( P = 0.0002). Logistic regression revealed a significant influence of peanut extract sensitization and region on the occurrence of systemic reactions ( P = 0.0185 and P = 0.0436, respectively). Conclusion: Sensitization to Ara h 1, 2 and 3 is usually acquired in childhood. IgE to Ara h 2 ≥ 1.0 kUA /l is significantly associated with the development of systemic reactions to peanut.